Correlation of Brixia Score Changes with Length of Stay in Patient with COVID-19 - Sutedjo, Verawati; Soewondo, Widiastuti; Erawati, Dini Rachma (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The increase in Covid-19 cases in Indonesia as well as the hospital length of stay is unpredictable. The degree of lung damage in Covid-19 largely determines the severity of the disease, a serial chest X-ray using Brixia score can be used to assess changes in pulmonary parenchymal damage and could predict the length of hospitalization. This study aims to analyze the correlation of Brixia score with the length of hospitalization in Covid-19 patients.Subjects and Method: This cross-sectional study was conducted at Sumber Waras Hospital from November 2021 until January 2022. The samples are Covid-19 confirmed patients who were treated at Sumber Waras hospital. Independent variable is Brixia score and dependent variable is length of hospitalization. Brixia's score assessment from two serial chest X-rays was divided into 4 categories: low to low, low to high, high to low, and high to high. All the categories were analyzed using Kruskall-Wallis method then continued with Mann-Whitney U test. The multivariate variable was analyzed using linear regression.Results: There are 190 samples, the median score of Brixia at the beginning of treatment is 4 (range 0-18), and the median score of Brixia on serial examination is 6 (range 0-18). Patients in low to low category had median 10 days length of hospitalization, low to high category and high to low category had median 11 days, and high to high category had median 8 days. There was no statistically significant correlation between Brixia score and length of hospitalization (p= 0.377).Conclusion: There is no significant relationship between the median Brixia score changes with the length of hospitalization of covid-19 patients.Keywords: Covid-19, hospitalized, Brixia score changes, length of stayCorrespondence: Widiastuti Soewondo. Faculty of Medicine Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Mobile: +6282134368592. Email: widiastuti.sprad56@staff.uns.ac.id.Indonesian Journal of Medicine (2022), 07(03): 262-268https://doi.org/10.26911/theijmed.2022.07.03.02